Partially Adaptive Econometric Methods and the Modern Obesity Epidemic - Scott A. Carson; James B. McDonald (Center for Economic Studies and ifo Institute (CESifo), 2018)
Assumptions about explanatory variables and errors are central in regression analysis. For example, the well-known method of ordinary least squares yields consistent and efficient estimators if the underlying error terms are independently, identically, and normally distributed. Additionally, the conditional distribution of the dependent variable is symmetric. The modern obesity epidemic is a well-known health dilemma where the BMI distribution was initially positively skewed but has become more symmetric, which may affect inferences about health and public resource allocation. This study applies partially adaptive estimation methods with flexible error distributions to account for possible skewness and leptokurtosis in the distribution of BMI.
Keywords: C10; D13; J13; 330; obesity epidemic; partially adaptive estimation; skewed generalized T distribution